Implementation of Billboard Tax Policy in the City of Bandung - Dian Permata Puspita; Mas Halimah; Hilman Abdul Halim (Jurnal Manajemen Pelayanan Publik, 2020)
This study was titled "Implementation of Billboard Tax Policy in the City of Bandung". This study was backed by the writer's interest in seeing the phenomenon of unachieved billboard tax revenue targets for the past few years, even the realization is below 11% of the target that was set in the City of Bandung. The purpose of this study was to find out and analyze the billboard tax policy implementation in the City of Bandung. This study applied the theory of Soren C. Winter that explains three factors that influence the process of policy implementation. This research used a qualitative research method.              The results showed that the implementation of the tax policy billboard in the city of Bandung had gone well but there were still obstacles in organizational and inter-organizational behavior, caused by the lack of coordination that existed between BPPD and Satpol PP. Furthermore, the behavior of the target group was also found that there were still negative responses from billboard organizers who are looking for loopholes so they can be detached from the imposition of billboard taxes. Meanwhile, on the other aspects, it had gone well, such as the street-level bureaucrat's behavior, namely through discretion which was done by making barcodes and working fast without waiting for recommendations from other SKPD to supervise billboards that are considered to be in violation. The commitment indicators of organizational and inter-organizational behavior have gone well because employees' actions were in line with the vision and mission of the organization and the last indicator of positive response to the behavior of the target group can be seen from the support of billboard organizers to help the government supervise and remind the public to be obedient on paying taxes.